Respuesta :

Answer:

3a-10

Step-by-step explanation:

MAYBE IT HELPS

Answer:

f(a - 4) = 3a - 10

Step-by-step explanation:

As given, we have here, an original equation: f(x) = 3x + 2.

To work out f(a - 4), we substitute x = a - 4 into original equation.

f(a - 4) = 3(a - 4) + 2

We apply the distributive property to keep going.

f(a - 4) = 3a - 3*4 + 2

We perform the multiplication of 3 and 4.

f(a - 4) = 3a - 12 + 2

We perform the addition of (-12) and 2 to finalize the answer.

f(a - 4) = 3a - 10

This is the final answer

I hope this helps!

ACCESS MORE